2018
DOI: 10.3892/ijmm.2018.3479
|View full text |Cite
|
Sign up to set email alerts
|

Madecassoside activates anti‑neuroinflammatory mechanisms by inhibiting lipopolysaccharide‑induced microglial inflammation

Abstract: Neurodegeneration is typically preceded by neuroinflammation generated by the nervous system to protect itself from tissue damage, however, excess neuroinflammation may inadvertently cause more harm to the surrounding tissues. Attenuating neuroinflammation with non‑steroidal anti‑inflammatory drugs can inhibit neurodegeneration. However, such treatments induce chronic side effects, including stomach ulcers. Madecassoside, a triterpene derived from Centella asiatica, is considered to be an alternative treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…These inhibitory effects were associated with the reduction of ROS level and stimulation of GSH content, indicating the role of RECA in oxidative balance. A study done by Sasmita et al [56] indicated that cells treated with the madecassoside at a maximum non-toxic dose (MNTD) were able to suppress the intracellular ROS generations by downregulating the gene and protein expression of pro-neuroinflammatory components. Therefore, the antioxidative properties observed in RECA could be attributed to the high proportion of madecassoside in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitory effects were associated with the reduction of ROS level and stimulation of GSH content, indicating the role of RECA in oxidative balance. A study done by Sasmita et al [56] indicated that cells treated with the madecassoside at a maximum non-toxic dose (MNTD) were able to suppress the intracellular ROS generations by downregulating the gene and protein expression of pro-neuroinflammatory components. Therefore, the antioxidative properties observed in RECA could be attributed to the high proportion of madecassoside in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that MA prevented the releases of proinflammatory cytokines by repressing the activation of MAPK and NF-kB signaling pathway and enhancing the expression of heme oxygenase-1 (HO-1) and nuclear factor E2related factor 2 (Nrf2) during LPS/D-GalN-induced liver injury (Wang et al, 2018). Other reports also demonstrated that MA had antineuroinflammatory effects and concentrationdependently restrained the expression of proinflammatory cytokines, nitric oxide synthase, cyclooxygenase-2, and nuclear factor kappa-B (NF-kB) pathway induced by LPS (Sasmita et al, 2018). Moreover, Cao et al also proved that MA prevented the LPS-induced sepsis and the protective mechanisms were associated with inhibiting inflammatory response induced by LPS (Cao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Madecassoside (MADE) is a major bioactive triterpenoid saponin isolated from Centella asiatica that has been found to exert various pharmacological activities including antioxidative effect [ 10–12 ]. MADE was reported to have the reactive oxygen species (ROS) scavenging activity [ 11 , 13 ]. MADE exerts protective effect on hydrogen peroxide (H 2 O 2 )-induced oxidative stress and autophagy in human melanocytes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%